The quest for odorants having salicylate notes. (20th September 2013) - Gaudin, Jean‐Marc
ABSTRACT We describe the synthesis and sensory characterization of a series of compounds which we anticipated would possess the olfactory notes of salicylates. We explored carba‐analogues, cyclic β‐keto esters and cyclic β‐diketones as salicylate analogues. Applying the simple concept of three‐dimensional structure similarity was very fruitful. Salicylate carba‐analogues and β‐keto esters, especially compounds 5, 7 and 10 for the first series and 27 and 28 for the second series, proved to be the most interesting type of compounds. For example, 1‐(2‐hydroxyphenyl)‐3‐phenyl‐1‐propanone (10), which can be found in nature, is nicely diffusive and has an excellent olfactory profile with an interesting dual floral–animal note. In general, these compounds may offer a first credible alternative to the popular salicylates. Copyright © 2013 John Wiley & Sons, Ltd.